Impact of a ping-pong ball. (20th March 2017) - Cross, Rod
Abstract: Measurements are presented of the impact time, peak force and centre of mass displacement of a ping-pong ball impacting vertically on a hard, horizontal surface. The results are compared with a recent measurement described in this journal.